Duplication cyst of the ileum presenting with severe anemia detected by double-balloon endoscopy - Takegawa, Yumi; Hiramatsu, Katsushi; Murata, Yosuke; Akazawa, Yu; Saito, Yasushi; Ozaki, Yoshihiko; Takahashi, Kazuto; Naito, Tatsushi; Ofuji, Kazuya; Matsuda, Hidetaka; Ohtani, Masahiro; Nemoto, Tomoyuki; Suto, Hiroyuki; Goi, Takanori; Imamura, Yoshiaki; Nakamoto, Yasunari (Endoscopy International Open, 2018)
Background and study aims Duplication cysts of the ileum are rare and present with non-specific clinical manifestations such as abdominal pain, vomiting, melena, and intussusception. Therefore, preoperative diagnosis is difficult. Here, we report a case of duplication cyst of the small intestine that was diagnosed preoperatively using double-balloon enteroscopy. A 19-year-old man presented with severe iron deficiency anemia, abdominal pain, and exertional dyspnea. Gastroscopy and colonoscopy revealed no remarkable findings. Abdominal computed tomography revealed a cystic structure in the ileum. Therefore, we performed double-balloon enteroscopy via the anal route. The intestinal tract was bifurcated, with one segment ending in a blind sac containing normal villi and an ulceration. Tc-99 m pertechnetate scintigraphy showed no accumulation in the lesion. Accordingly, we diagnosed a duplication cyst and suspected that this was the cause of severe anemia. Following small bowel resection with cyst excision and anastomosis, the anemia and presenting symptoms resolved. This report highlights the usefulness of double-balloon enteroscopy of the small intestine for preoperative diagnosis of the obscure gastrointestinal bleeding, including duplication cysts.